Implementation of Article 1368 of the Indonesian Civil Code in Settling Disputes Over Crop Damage Caused by Livestock in Nagori Dolok Ilir II, Dolok Batu Nanggar District - Muhammad Fachryan Arbi; Sarles Gultom; Parlin Dony Sipayung (Academic Solution Publisher, 2024)
This study investigates the conflict that occurred in Nagori Dolok Ilir II, Dolok Batu Nanggar District, between agricultural land owners and livestock owners. The study also investigates the application of Article 1368 of the Civil Code as a relevant solution. The research method involves conducting a survey to identify the problem. After that, we see how Article 1368 of the Civil Code can help resolve the conflict. The results show that respondents really understand how livestock affect the environment and agriculture. To determine who is responsible for crop losses, Article 1368 of the Civil Code is considered appropriate and relevant. One of the suggestions put forward is to increase government supervision of livestock, increase awareness of livestock owners, and provide ongoing education programs on livestock management. This study improves understanding of resolving legal conflicts related to livestock damage to crops.